Fiscal Policy and Economic Growth : Lessons for Eastern Europe and Central Asia - Gray, Cheryl; Lane, Tracey; Varoudakis, Aristomene (Washington, DC: World Bank, 2012)
This study explores public finance policies in the transition countries of Europe and Central Asia (ECA) and their likely effects on economic growth. The analysis is organized in three parts. Part one reviews public finance systems across the ECA region with regard to overall size, structure of expenditures and revenues, and patterns of fiscal adjustment over time. It compares these patterns and trends in ECA countries against those in fast-growing economies in other regions, and it explores possible relationships between these public finance variables and rates of economic growth. Part two undertakes detailed analysis of public expenditures policies in four major areas: infrastructure, education, health, and pensions. Part three turns to the revenue side of the budget and looks in detail at two issues of particular importance in current policy debates: the impact of flat income tax reforms and the level and structure of taxes on labor.